Tinjauan Mendalam Pengaruh Insufisiensi Renal terhadap Major Adverse Car- diovascular Event (MACE) dan Mortalitas pada Pasien Infark Miokard Akut Ele- vasi Segmen St (IMA-EST) - Nurudinulloh, Akhmad Isna; Anjarwani, Setyasih (RSUD Dr. Saiful Anwar Province of East Java, 2024)
The widespread implementation of invasive procedures such as coronary angiography and primary percutaneous coronary intervention (PCI) into the routine management of patients with acute ST-segment elevation myocardial infarction (STEMI) in the last 10 years has led to a significant improvement in patient prognosis. At the same time, this also raises new problems and questions, mostly related to the fact that there are many elderly patients and/or patients with comorbidities who need to undergo this invasive procedure. One of the most important comorbidities is renal insufficiency. STEMI patients with renal insufficiency typically present with more extensive atherosclerotic lesions, including diffuse coronary calcification, which poses a challenge to the interventional cardiologist due to a higher risk of periprocedural complications, higher risk of restenosis, major adverse cardiovascular event (MACE) , and patient mortality. This review discusses in depth the influence of renal insufficiency on MACE and mortality in STEMI patients. Keywords: renal insufficiency, STEMI, MACE, mortality.